2011
DOI: 10.7863/jum.2011.30.7.1003
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Study on 3‐Dimensional Sonography for the Prenatal Diagnosis of Central Nervous System Defects

Abstract: Among centers with technical expertise, remote review of 3D sonographic volumes of the fetal CNS resulted in an accurate and reliable method for diagnosis of fetal brain malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“…Although stored volume data sets are large, up to 10 megabyte, they can be compressed to about 15 to 20% of the original file size and submitted via Digital Imaging and Communications in Medicine (DICOM) technology for off-line consultation without noticeable loss of details or image quality 1 . Moreover, volume data sets can be shared by expert on dedicated website and be used in multicenter studies while demonstrating a high sensitivity and reliability 2,3 . 3DUS with its applications allow operators a simultaneous and less time consuming (when compared with 2DUS) rendering of the anatomical landmarks in three orthogonal planes when using the multiplanar mode.…”
mentioning
confidence: 99%
“…Although stored volume data sets are large, up to 10 megabyte, they can be compressed to about 15 to 20% of the original file size and submitted via Digital Imaging and Communications in Medicine (DICOM) technology for off-line consultation without noticeable loss of details or image quality 1 . Moreover, volume data sets can be shared by expert on dedicated website and be used in multicenter studies while demonstrating a high sensitivity and reliability 2,3 . 3DUS with its applications allow operators a simultaneous and less time consuming (when compared with 2DUS) rendering of the anatomical landmarks in three orthogonal planes when using the multiplanar mode.…”
mentioning
confidence: 99%
“…3D methods bring new significant data in a short period of time; the data are reproducible once the volume has been acquired and can be reanalyzed [18]. The 3D acquisition allows the navigation inside the volume and the reconstruction of particular sections or the achievements of high significant condensed volumes [19].…”
Section: D Versus 3d Techniquesmentioning
confidence: 99%
“…A multicenter study that had included 11 centers found the following values for the detection of fetuses with CNS defects at 18 gestation weeks: the sensitivity-93.3% with a specificity of 96.5% with an excellent intercenter agreement [18].…”
Section: Ultrasound Versus Mrimentioning
confidence: 99%
“…Fetal central nervous system (CNS) defects are amongst the commonest congenital structural anomalies [1][2][3]. Standard protocols for the routine 20-week anomaly scan involve axial 2-D assessment of the fetal brain allowing detection of about 80% of congenital CNS defects [1,4,5].…”
Section: Introductionmentioning
confidence: 99%